Aplikasi Manajemen Strategi dengan Pendekatan Balanced Scorecard (Studi pada Lembaga Penjaminan Mutu Pendidikan Provinsi Bali) - Santhi, Made Widya; Rahayu, Mintarti; Noermijati (Universitas Brawijaya, Indonesia, 2013)
The study aims to describes the members of the public sector organizations understanding, namely Lembaga Penjaminan Mutu Pendidikan (LPMP) Bali on strategic management framework with a balanced scorecard approach and identify challenges of the balanced scorecard implementation in LPMP Bali Province. The research method is descriptive qualitative case study approach, the informants all officials in the structural and functional LPMP Bali Province. The results showed that members of the organization LPMP understand framework strategy management with the balanced scorecard approach as a framework that can provide useful information and can help every member of the organization in making better decisions. By using a balanced scorecard approach, LPMP Bali is expected to improve the effectiveness and efficiency in providing services to stakeholders. The challenge in the application of the balanced scorecard in LPMP Bali, the members of the organization feel comfortable with the old habits that lack the motivation to make changes in work culture, mindset and habits that they have done so far.